PENGARUH KUALITAS PELAYANAN DAN DISIPLIN KERJA TERHADAP KEPUASAN PASIEN RAWAT INAP PADA RUMAH SAKIT UMUM DAERAH KABUPATEN LAHAT - Andayani, Melia (Universitas Muhammadiyah Palembang, 2021)
Purpose – The purpose of this study was to determine the effect service quality and work dicipline on inpatient satisfaction in Lahat district Hospital Design/methodology –The research design used in this study is a quantitative method with a causal associative research method, namely to determine whether to know the effect between two or more variables. The data analysis methods used are Multiple Linear Regression Analysis, Parsial test (t) and Simultaneus test (f).Findings -Based on the test results, the regression coefficient for the variable service quality (X1) is 0.297, employee work discipline (X2) is 0.296, and the constant value is 13.162, so the regression equation for this study is: Y = 13.162 + 0.297 X1 + 0.296 X2. From the results of the partial test (t test) the variable service quality (X1) t count 2.891> t table 2.002 or and a significant level of 0.05 means that service quality has a significant effect on patient satisfaction (Y). And from the results of the partial test (t test) variable employee work discipline (X2) t count 2.980> t table 2.002 and a significant level of 0.004 means that employee work discipline has a significant effect on patient satisfaction (Y). Meanwhile, from the ANOVA test or F test, it is found that F counts 9.143 with a probability of 0.000 (P value < ?), so Ho is rejected and Hi is accepted. So, the variables of service quality and work discipline of employees together (simultaneously) have a significant effect on patient satisfaction at the Lahat District General Hospital.